Influence of slicing tools on quality of 3D printed parts. Issue 1 (2nd January 2016) - Baumann, Felix; Bugdayci, Halil; Grunert, Jonas; Keller, Fabian; Roller, Dieter
ABSTRACT: With slicing tools it is possible to convert digital 3D models into printing instructions for 3D printers. The general approach is: The model is cut into horizontal slices which are then used to create extrusion paths similar to milling paths in the traditional CNC field, which are then being filled with material, mostly plastic material. The goal of this study is to compare available slicing tools for 3D printers under defined aspects using different configurations. The main contributions of this study are: (1) collecting methods and tools to judge print results, (2) analysis of the available slicing tools with appropriate tests and comparisons, and (3) evaluating the slicing tools using the analysis as solid foundation. GRAPHICAL ABSTRACT: